TEACHERS PERCEPTION OF CHARACTER EDUCATION INTEGRATION IN LEARNING LANGUAGE - Atmazaki Atmazaki; Agustina Agustina; Vivi Indriyani; Abdurahman Abdurahman (LPPM Universitas Negeri Yogyakarta, 2020)
Education in the 21st Century currently requires students to be intelligent and of character. Because of the various demands that teachers must have in order to meet all current learning goals, knowledge and skills, sometimes the teacher forgets to focus on shaping student character. This is reflected in the increasing crime, violations of human rights, legal injustice, and various forms of bad behavior that are increasingly reaching all sectors of life. The teacher has an important role to overcome these problems. Based on this background, this study aims to determine teacher perceptions regarding the formation of student characters. This research is a descriptive study with a questionnaire collection technique. The instrument used was a questionnaire sheet. The questionnaire was developed via Google form and distributed online through social media whatsup on the group discussion group of English subjects in West Sumatra. The number of respondents who filled out the questionnaire was 62 teachers. The results show that for now some teachers have integrated the strengthening of student character through intracuricular, extracurricular, and non-curricular activities.